(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article focuses on the analysis of sentences with monovalent syntactic units in the position of the non-nuclear dependent (ÑD) component in the structure of English and Uzbek sentences; by means of componential and junctional models the researcher identifies the morphological features and syntactic relationships, the connection possibilities with other syntactic units of ÑD components. The article can take interest of researchers working on functional linguistics as well as those who learn the English language.